Ownership Structure and Firms Performance : A Case Study in Palestinian Listed Corporations - Hajjaj, Mohammed Abdul Alkareem Rezeq (2009)
This project investigates the association among ownership structure and firm performance of Palestinian’s listed companies. The data collected for this research is for the period 2003-2007 and the sample consists of 37 companies. Five specific research questions are applied to investigate the associations among the vote fraction held by controlling shareholder/shareholders and performance and vote differentiation and performance. The performance procedures employed are stock return, ROA, ROE and Tobin’s Q. The outcome specify that corporations with a dispersed ownership structure, (i.e. the largest shareholder holds less than 20% of total votes), are connected with worse performance concerning stock return, ROA and ROE, but are greatly valued relating to Tobin’s Q. This research points out that the association among vote concentration and performance might be spurious. When reflect on firm specific factors, and categorizations of the controlling shareholder appear to engage in recreation vital role. Further this research demonstrates that the associations among vote concentration and performance vanish, when consider other vote shareholders exceeding different thresholds (5, 10 and 20%). In line with previous research, the present study finds that vote differentiation does not affect firm performance. Instead risk and size of the company are decisive in the extent to which companies apply vote differentiation tools.